1989
DOI: 10.1104/pp.90.1.101
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucose: (1,3)-β-Glucan Synthase from Daucus carota L.

Abstract: The membrane-bound UDP-glucose-fl-(1, branes, up to 80% of the enzyme was released with 0.7% CHAPS. Solubilized enzyme was stable for at least 9 hours at 40C. When more highly purified membrane fractions were isolated from sucrose step gradients a slightly different picture emerged. Activity from the 20/30% interface (Golgi and tonoplast enriched) was readily solubilized and expressed. Activity from the 30/40% interface (plasma membrane enriched) was also solubilized; however, it was necessary to add heat inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…This was consistent with the property of the phosphoglucomutase . Labelling of proteins with a similar apparent molecular mass has also been detected in other plant systems (Lawson et al, 1989).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This was consistent with the property of the phosphoglucomutase . Labelling of proteins with a similar apparent molecular mass has also been detected in other plant systems (Lawson et al, 1989).…”
Section: Discussionmentioning
confidence: 86%
“…The 30 kDa family includes the 30 and 31 kDa proteins of Italian ryegrass, a 31 kDa protein from soybean and a 34 kDa protein from cotton (Meikle et al, 1991 ;Fink et al, 1990;Delmer et al, 1991). The 55 kDa family contains a doublet with molecular mass of 54 and 58 kDa in Italian ryegrass, a 57 kDa protein in both carrot and red beet, a 52 kDa protein in cotton and a 55 kDa protein from pea (Delmer et al, 1991 ;Dhugga & Ray, 1991;Frost et al, 1990;Lawson et al, 1989;Meikle et al, 1991). Two proteins labelled from A .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports of use of UDP-[3H]pyridoxal as labeled probe; in the first (22), a polypeptide of 42 kD from mung bean membranes was labeled, but labeling did not meet all the criteria expected for the catalytic subunit of callose synthase; a second report (19) indicated that a number of membrane proteins from red beet could be labeled; when the specificity of labeling was improved by a substrate protection technique, these were reduced to labeling ofpolypeptides of 200, 76, 60, and 57 kD. Wasserman's group also demonstrated the feasibility of using 5-azido-[32P]UDPglucose as an affinity labeling probe (16) and, in subsequent work using this probe (9), concluded that the 57 kD polypeptide of red beet is the most likely candidate for catalytic subunit of the enzyme based upon its enrichment upon product entrapment (see 13), its pH optimum for labeling, and its effector requirements.…”
mentioning
confidence: 99%